The Role of Digital Literacy and Financial Literacy on the Use of Islamic Fintech Moderated by Religiosity the Impact on Personal Financial Management - Aziz, Abdul; Giantoro Pamungkas; Alifa, Naufal Luthfi; Wendy Wijaya; Layaman (MultiTech Publisher, 2023)
Financial management skills are a very important and necessary topic, because currently Indonesians, including Cirebon's digital natives (millennials and generation Z), still do not realise the importance of good financial management habits. Sharia financial technology is one of the digital financial innovations that is useful as a personal financial management tool for its users wherever and whenever they are. However, the development of Islamic fintech is still far behind compared to conventional fintech. This study aims to determine the effect between digital literacy and financial literacy on the use of Islamic fintech moderated by religiosity and its impact on personal financial management. This research was conducted with a quantitative method, using a moderated mediation analysis model. The results showed that digital literacy has a significant positive effect on the use of Islamic fintech, but financial literacy has no positive effect. Meanwhile, religiosity cannot moderate the relationship between digital literacy and the use of Islamic fintech and the relationship between financial literacy and the use of Islamic fintech. And the use of Islamic fintech has an influence on personal financial management.